Urgency of Falsum in Indonesian Criminal Justice System as Basis for Revision; An Islamic Perspective - Mia Amiati; Taufik Rachman; R.B. Muhammad Zainal Abidin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
In Indonesian Islamic law, "falsum" has no direct equivalent. However, this idea matters in legal debates of beliefs, utterances, and behaviors. Falsum corrects final decisions in Germany and the Dutch during Revision. Indonesian prosecutors might request Revision, but the Constitutional Court limited this power to convicts and their descendants, extending unfairness. Revision should remedy bribery, document forgery, conflict of interest, and perjury by using the idea of falsum. However, falsum implementation in Indonesia raises problems about its compatibility with Islamic values. The study investigates how addressing falsum, in accordance with the principles of justice and utility, can lead to fairer legal reforms and bolster public confidence in the judiciary, especially within Indonesia's predominantly Muslim community. It examines the possibilities and drawbacks of legalizing falsum in Indonesia using normative, theoretical, and comparative approaches. It contends that the notion of falsum can provide a persuasive rationale for legal reforms in Indonesia's criminal court system. It also enables law enforcement officials and future drafters of the Criminal Procedure Code (KUHAP) to understand the evolution of Revision because granting prosecutors the authority to initiate Revision based on falsum is crucial for ensuring greater justice.